Alleviation of soil acidity in Ultisol and Oxisol for corn growth - Ismail, H.; Shamshuddin, J.; Syed Omar, S. R. (Springer, 1993)
Malaysian Ultisols and Oxisols are characterized by low pH, high soil solution Al concentration and Ca and/or Mg deficiencies, which are limiting to corn growth. An experiment was conducted to determine the changes in solid and soil solution phase properties of a representative Ultisol and Oxisol following applications of ground magnesium limestone (GML), gypsum and their combinations, and their effects on corn growth. A plot of pAl against lime potential (pH-1/2 pCa) showed that the points were mostly positioned between the theoretical lines for kaolinite-quartz and gibbsite equilibrium, reflecting the kaolinitic-oxidic mineralogy of the Ultisol and Oxisol. Gypsum application increased Al concentration in the soil solutions of the Ultisol, but had no significant effect on that of the Oxisol. The increase in Al concentration in the Ultisol was due to an increase in ionic strength. Gypsum application increased soil solution pH of the Oxisol due to release of OH as a result of ligand exchange between SO4 and OH ions on the oxides of Fe and/or Al. Exchangeable Al in both soils was reduced by gypsum application. The reduction was associated with solid phase immobilization through alunite formation; the soil solutions of soil samples treated with 2 and 4 t gypsum ha-1 were supersaturated with respect to alunite. Application of GML at 2 t ha-1 together with 1-2t gypsum ha-1 gave high top weight of corn. Relative top weight of corn was positively correlated with a soil solution Mg and Ca/Al concentration ratio, but negatively correlated with soil solution Al concentration. Foliar Al corn was positively correlated with soil solution Al concentration. Soil solution Al and Mg concentrations, and Ca/Al concentration ratio can be used as indices of soil acidity in Ultisols and Oxisols. ei]{gnB E}{fnClothier}